Adaptive oriented PDEs filtering methods based on new controlling speed function for discontinuous optical fringe patterns. (January 2018) - Zhou, Qiuling; Tang, Chen; Li, Biyuan; Wang, Linlin; Lei, Zhenkun; Tang, Shuwei
Highlights: We redefine a new controlling speed function to depend on the orientation coherence, and the orientation coherence can be used to distinguish the continuous regions and the discontinuous regions. The proposed adaptive OPDEs based on the new controlling speed function are suitable for discontinuous optical fringe patterns. The proposed adaptive OPDEs can preserve the integrity of fringes for the continuous regions, and same time to preserve the discontinuity for the discontinuous regions while filtering. Abstract: The filtering of discontinuous optical fringe patterns is a challenging problem faced in this area. This paper is concerned with oriented partial differential equations (OPDEs)-based image filtering methods for discontinuous optical fringe patterns. We redefine a new controlling speed function to depend on the orientation coherence. The orientation coherence can be used to distinguish the continuous regions and the discontinuous regions, and can be calculated by utilizing fringe orientation. We introduce the new controlling speed function to the previous OPDEs and propose adaptive OPDEs filtering models. According to our proposed adaptive OPDEs filtering models, the filtering in the continuous and discontinuous regions can be selectively carried out. We demonstrate the performance of the proposed adaptive OPDEs via application to the simulated and experimental fringe patterns, and compare our methods with the previous OPDEs.